2023
DOI: 10.1177/23821205231173289
|View full text |Cite
|
Sign up to set email alerts
|

Academic and Wellness Outcomes Associated with use of Anki Spaced Repetition Software in Medical School

Jillian K Wothe,
Lindsey J Wanberg,
Rae D Hohle
et al.

Abstract: OBJECTIVES Medical students are increasingly using a spaced repetition software called Anki to study. There are limited studies evaluating the relationship between Anki and learner outcomes. In this study, we describe the history of Anki use in medical school and assess the potential relationships between use of Anki and medical student academic, extracurricular, and wellness outcomes. METHODS We used cross-sectional data from a 50-item online survey and retrospective academic performance data from our institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…25,26 Now, many students have traded textbooks for third-party resources and spaced-repetition flashcards. 27,28 With the rising popularity of LLMs, medical students andresidentsnowhaveanewtooltoaddtotheirstudyarsenalassome learners have been asking chatbots to simplify complex concepts for them. 29 Surgeonsinvolvedinmedicaleducation,whetherworkingwith medical students or residents, can use LLMs to assist in generating learning objectives and cases for didactic learning purposes.…”
Section: Medical Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Now, many students have traded textbooks for third-party resources and spaced-repetition flashcards. 27,28 With the rising popularity of LLMs, medical students andresidentsnowhaveanewtooltoaddtotheirstudyarsenalassome learners have been asking chatbots to simplify complex concepts for them. 29 Surgeonsinvolvedinmedicaleducation,whetherworkingwith medical students or residents, can use LLMs to assist in generating learning objectives and cases for didactic learning purposes.…”
Section: Medical Educationmentioning
confidence: 99%
“…Even before the COVID-19 pandemic, technologic improvements created a shift in the delivery of medical education . Now, many students have traded textbooks for third-party resources and spaced-repetition flashcards . With the rising popularity of LLMs, medical students and residents now have a new tool to add to their study arsenal as some learners have been asking chatbots to simplify complex concepts for them .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Wothe et al demonstrated in 165 students surveyed, daily Anki use was correlated with increased Step 1 scores, but not Step 2 scores. Interestingly, they found an association between Anki use and increased sleep quality [ 20 ] Sun et al, however, did not find benefit of flashcard use in a medical student psychiatry course, but this may have been due to the short 1-month interval of the study [ 16 ]. Within residency education, both medicine and surgery subspecialty residents are using Anki for preparation for in-service exams, and studies have demonstrated strong positive correlation with examination scores [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical students complete much of their preclinical didactic learning outside of the classroom, with the assistance of third-party resources such as Anki flashcard decks, instead of traditional lectures [ 3 ]. Anki flashcard decks use the principle of spaced repetition to improve memorization [ 4 , 5 ]. Medical students found Anki flashcards produced for their specific curriculum helpful and believed that these flashcards reduced anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Use of crowdsourced flashcard decks eliminates the investment of time required upfront to produce flashcards for each lecture, but these flashcards are not specific to the user’s medical school curriculum [ 4 ]. A mechanism to match existing flashcards, created and vetted by medical students within the Reddit and AnkiHub communities, to the learning goals of didactic lectures delivered by medical school faculty members would be less time-intensive for faculty and students.…”
Section: Introductionmentioning
confidence: 99%